Pengaruh pH dan Konsentrasi terhadap Adsorpsi Ion Logam Cr³⁺ menggunakan Silika Xerogel dari Abu Terbang - Putri Nugraha; Edi Nasra (MASALIQ, 2025)
Fly ash, a byproduct of coal combustion produced continuously, poses significant environmental risks if not utilized effectively. Its high silica content presents potential for conversion into silica xerogel, which can function as an adsorbent for heavy metal ions such as Cr³⁺. This study aims to analyze the SiO₂ content in synthesized silica xerogel using X-Ray Fluorescence (XRF) analysis and to determine its optimum adsorption capacity based on variations in pH and Cr³⁺ ion concentration. Optimization was carried out at varying pH levels (2–6) and concentrations (100–300 ppm). XRF analysis revealed that the SiO₂ content in fly ash pretreated with 3M HCl was 54.167%, while the synthesized silica xerogel exhibited an increased SiO₂ content of 69.09%, with a %yield of 54.825%, indicating a relatively high silica purity. Adsorption tests showed maximum adsorption capacity at pH 4 and a Cr³⁺ concentration of 200 ppm, reaching 26.76 mg/g. The adsorption isotherm followed the Langmuir model with a determination coefficient of R² = 0.9509, indicating a strong fit between the model and the experimental data. These findings suggest that silica xerogel derived from fly ash holds promise as an effective adsorbent for heavy metal wastewater treatment. Keywords: Fly Ash; Adsorption; Silica Xerogel; Cr³⁺ Metal Ion; Langmuir Isotherm